2023
DOI: 10.3389/fmmed.2023.1143298
|View full text |Cite
|
Sign up to set email alerts
|

Human brain organoid code of conduct

Abstract: Human brain organoids are models derived from human embryonic or induced pluripotent stem cells that mimic basic cerebral microanatomy and demonstrate simple functional neuronal networks. Brain organoids have been a rapidly expanding avenue for biomedical research in general and specifically: neural development, regeneration, and central nervous system pathophysiology. However, technology replicating functional aspects of the human brain, including electrically active neural networks, requires a responsible co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…The report identifies three models of human brain research: human neural organoids, human neural transplants, and human-animal neural chimeras. The use of brain organoids in research raises ethical concerns; these include the possible need for stringent research restrictions and formal ethical oversight for advanced brain organoids as well as aspects of consciousness, interaction with social environments, and implantation in animals (de Jongh et al, 2022;Hoppe et al, 2023). Researchers, policymakers, and bioethicists are called upon to work together from the early stages of research and development onwards to identify emerging ethical questions and take new directions.…”
Section: Brain Organoids and Organoid Intelligence As The New Ethical...mentioning
confidence: 99%
“…The report identifies three models of human brain research: human neural organoids, human neural transplants, and human-animal neural chimeras. The use of brain organoids in research raises ethical concerns; these include the possible need for stringent research restrictions and formal ethical oversight for advanced brain organoids as well as aspects of consciousness, interaction with social environments, and implantation in animals (de Jongh et al, 2022;Hoppe et al, 2023). Researchers, policymakers, and bioethicists are called upon to work together from the early stages of research and development onwards to identify emerging ethical questions and take new directions.…”
Section: Brain Organoids and Organoid Intelligence As The New Ethical...mentioning
confidence: 99%
“…If so, it seems to follow that the life of a transplanted animal who had accidentally achieved full moral status should not be terminated, as commonly happens to monkeys used in brain research, for purposes of tissue histology, for instance [34,35]. Rather, the neural chimera in question should be retired to an animal sanctuary [36] or other suitable setting, and should not be used in any further invasive research, even if these constraints happened to conflict with some of the original goals of the study.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Moving forward to the use of brain organoids, numerous protocols for generating brain organoids have been published which mainly aim to establish the disease modeling on brain disorder. For biomedical study in general and in particular on neural development, regeneration, and pathology of the central nervous system, brain organoids have been a fast growing field ( Hoppe et al, 2023 ). One of them is the neural organs produced from human PSCs, which serves as a platform for studying brain tumors.…”
Section: The Advantages and Limitations In Modeling Neurodegenerative...mentioning
confidence: 99%
“…However, despite the drawbacks of brain organoid systems, which are difficult to grow, labor- and money-intensive, lack a vascularization and blood circulation system which may cause the supply for oxygen and nutrients become restricted thus inducing necrosis in the center part of organoids ( García-Delgado et al, 2022 ; Xu et al, 2023 ) have complex physiological contexts of the intact human brain, and need to be addressed. Recent research has shown that endothelial cells can construct vascular networks in brain organoids, but their functioning is limited because neurons and their progenitors have high metabolic demands, limiting the size of brain organoids to a few millimeters ( Hoppe et al, 2023 ). Organoids can exchange nutrients and waste to the point where they transcend the limitations of diffusion.…”
Section: The Advantages and Limitations In Modeling Neurodegenerative...mentioning
confidence: 99%